Notas sobre as produções de bebidas e as transformações das paisagens nos sertões do Oeste do Brasil (1760-1830) (Revista de História Regional, 2020)
In the last decades of the 18th century and first decades of the 19th century, a series of transformations of political and social order implies important modifications in the way the Portuguese Crown, and after the Brazilian Empire look at the domain of the space and the colonization of its immense “sertão”, the backlands of the Empire, applying more efforts in its agricultural productions. As a result of this process occur important transformations in the practices and representations of the space and toward the landscape in a more intense process of colonization, aiming to convert in secure places the spaces and the landscapes to the adventitious. In this paper we aim to analyze through travel narratives, letters and maps how this process take place especially with the presence more constant of vineyards in the Extreme West of Portuguese America, then Empire of Brazil. Through the perspective of environmental history we aim to analyze and take some notes about the transformations in the landscape and the ecological modifications in the process of colonization. Here we aim to discuss mainly the descriptions and practices with indigenous alcoholic beverages and the transplantation of species of vegetables toward this process of domestication of environment and landscape, especially the narratives and reports about the introduction of vineyards to the local production of vine. At last, we aim to discuss some of the representations of the space in the expansion toward West of Brazil in the beginning of 19th century.